THE IMPACT OF AUTOMATION ON THE FIELD OF ACCOUNTING. - Keenoy, C. L. (The Accounting Review, 1958)
Abstract The advent of electronics in record-keeping and data-processing has placed the office equipment industry in the most challenging, yet potentially rewarding, role in its history. And the same thing can be said for accountants. Electronics is a new mode of transportation. Because of its tremendous speed in carrying out the errands, the electron can take one just about anywhere, statistically speaking. This revolution in office procedures and data-processing, promises to do for man's mind what the industrial revolution did for his body. By harnessing the electron, one will be able to multiply a single clerical employee's efforts many times. In a few more years American business would have been figuratively snowed under by its ever mounting volume of paperwork. At the start of the 20th century, only one man in every 40 employees was a paper worker. With pen and ink as his chief tools, this early-day clerical was able to keep up with all of the demands placed on accounting by business.